Photonic Approach for Generation and Fast Switching of Binary Digitally Modulated RF Signals - Xia Feng; Lianshan Yan; Peng Li; Jia Ye; Xihua Zou; Wei Pan; Bin Luo (IEEE Photonics Journal, 2020)
A photonic method to generate hybrid binary digitally modulated radio frequency (RF) signals (i.e. ASK, PSK, and FSK) by using a polarization-division-multiplexed Mach-Zehnder modulator (PDM-MZM) is proposed. The PDM-MZM is driven by two RF signals with different carrier frequencies and two multiplied digital signals. By properly controlling the offsets and the amplitudes of the digital signals, ASK, PSK, and FSK signals can be generated and switched fastly. RF signals at 4/6 GHz and 10/15 GHz with switchable modulation formats are experimentally generated. Moreover, the performances of the generated signals are evaluated in a wireless transmission system and corresponding bit error rate (BER) curves of the signals are presented.